Bathsheba, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
Postcard showing a view of the hills and houses on the landscape. In the foreground there is a partial view of the railway tracks. This a divided back postcard. On the back of the postcard AL H £4 (Handwritten in pencil). A view of Bathsheba, Barbados.
Landscape; Black & white; 3 ½” x 5 ½”
Keywords: Seascapes; Beaches; Hills; Houses; Trees; Buildings; Coastlines; Landscapes